Licensed and Unlicensed NK Cells: Differential Roles in Cancer and Viral Control - Tu, Megan M.; Mahmoud, Ahmad Bakur; Makrigiannis, Andrew P. (Frontiers in Immunology, 2016)
NK cells are known for their well characterized ability to control viral infections and eliminate tumor cells. Through their repertoire of activating and inhibitory receptors, NK cells are able to survey different potential target cells for various surface markers, such as MHC-I—which signals to the NK cell that the target is healthy—as well as stress ligands or viral proteins, which alert the NK cell to the aberrant state of the target and initiate a response. According to the “licensing” hypothesis, interactions between self-specific MHC-I receptors—Ly49 in mice and KIR in humans—and self-MHC-I molecules during NK cell development is crucial for NK cell functionality. However, there also exists a large proportion of NK cells in mice and humans which lack self-specific MHC-I receptors and are consequentially ‘unlicensed’. While the licensed NK cell subset plays a major role in the control of MHC-I-deficient tumors, this review will go on to highlight the important role of the unlicensed NK cell subset in the control of MHC-I-expressing tumors, as well as in viral control. Unlike the licensed NK cells, unlicensed NK cells seem to benefit from the lack of self-specific inhibitory receptors, which could otherwise be exploited by some aberrant cells for immunoevasion by upregulating the expression of ligands or mimic ligands for these receptors.